Topical application of heparin for the correction of ocular surface lesions - V.D. Yartsev (РМЖ "Клиническая офтальмология")
Yartsev V.D. Scientific Research Institute of Eye Diseases, Moscow The article considers historical aspects of topical application of heparin in ophthalmology, it provides the description of anti-inflammatory action mechanism of heparin. The study describes in detail the indications for application of heparin ointment or heparin eye-drops in mono- or complex-therapy of dry eye syndrome, traumatic and burn keratitis, in some types of keratopathy. The experience of Russian and foreign researchers is analyzed (51 source in total). The author comes to the conclusion that topical use of heparin is pathogenically justified in the treatment of different inflammatory, dystrophic and degenerative conditions of ocular surface. Special attention is given to the treatment of patients with corneal burn. Disinfectant properties of heparin were found to be useful for etiotropic treatment of the patients with conjunctivitis or keratitis in mono- or combined therapy. The new drug forms of heparin, such as ocular ointment and eye drops, enable to choose the dose of the drug individually and accurately for the patients with different pathology of ocular surface, thus personifying the treatment. Key words: heparin, artificial tear, ocular surface, dry eye syndrome, keratopathy, corneal burn, PARIN-POS®, HYLOPARIN-COMOD®. For citation: Yartsev V.D. Topical application of heparin for the correction of ocular surface lesions. RMJ “Clinical ophthalmology”. 2018;2:97–101.